2016
DOI: 10.1051/0004-6361/201527251
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional simulations of gravitationally confined detonations compared to observations of SN 1991T

Abstract: The gravitationally confined detonation (GCD) model has been proposed as a possible explosion mechanism for Type Ia supernovae in the single-degenerate evolution channel. It starts with ignition of a deflagration in a single off-centre bubble in a near-Chandrasekharmass white dwarf. Driven by buoyancy, the deflagration flame rises in a narrow cone towards the surface. For the most part, the main component of the flow of the expanding ashes remains radial, but upon reaching the outer, low-pressure layers of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
92
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 91 publications
16
92
1
1
Order By: Relevance
“…56 Ni distributions are also shown for the DDT explosion models of Seitenzahl et al (2013), with similar 56 Ni masses, as dashed lines. The GCD model of Seitenzahl et al (2016) is shown as a dash-dot line. Light curves for our model and SN 2012fr are shown in the LSQ band, while the DDT model is shown in the V-band, which our modelling shows is extremely similar to LSQ.…”
Section: Chandrasekhar-mass Explosions and Extended 56 Ni Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Ni distributions are also shown for the DDT explosion models of Seitenzahl et al (2013), with similar 56 Ni masses, as dashed lines. The GCD model of Seitenzahl et al (2016) is shown as a dash-dot line. Light curves for our model and SN 2012fr are shown in the LSQ band, while the DDT model is shown in the V-band, which our modelling shows is extremely similar to LSQ.…”
Section: Chandrasekhar-mass Explosions and Extended 56 Ni Distributionsmentioning
confidence: 99%
“…Indeed, the twodimensional explosion simulations of Meakin et al (2009) consistently produce ∼1.1 M of 56 Ni. Seitenzahl et al (2016) obtain the lower 56 Ni mass of 0.74 M for GCD200 by assuming the initial deflagration is ignited far from the centre of the white dwarf. Larger offsets could potentially produce lower 56 Ni masses, however this may be unrealistic (e.g.…”
Section: Chandrasekhar-mass Explosions and Extended 56 Ni Distributionsmentioning
confidence: 99%
“…The carbon mass fraction impacts the overall energy release, expansion velocity, silicon-group and irongroup ejecta profiles (Calder et al, 2007;Höflich et al, 1998;Miles et al, 2016;Raskin et al, 2012;Röpke et al, 2006;Seitenzahl et al, 2016) in progenitor systems involving either one white dwarf (single degenerate channel) or two white dwarfs (double degenerate channel).…”
Section: A Helium Burning In Low-and Intermediate Mass Starsmentioning
confidence: 99%
“…For this type of explosion model, detailed nucleosynthesis calculations that go beyond a basic 13 isotope α-network have been presented for 2D simulations by Meakin et al (2009) and for 3D simulations by Seitenzahl et al (2016). A key signature of GCD models is that although it is technically a near-M ch explosion model, very little mass is burned in the deflagration.…”
Section: Gcd and Prd Modelsmentioning
confidence: 99%